CARBON REGULATION IN KAZAKHSTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article presents data on carbon regulation in Kazakhstan. The European Climate Change Programme (EHRC) to identify the most environmentally friendly and cost-effective measures designed to assist the EU in fulfilling its obligations under the Kyoto Protocol, in which special emphasis was placed on energy efficiency issues.
Keywords: climate change, greenhouse gases, standards, EU, energy audit, certification, car-bon intensity, potential, unconventional energy sources, renewable energy sources.